2021
DOI: 10.25259/ijpc_110_21
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Radiofrequency of Stellate Ganglion for Neuropathic Pain Associated with Recurrent Pleural Leiomyosarcoma - A Case Report

Abstract: Pleural leiomyosarcomas are rare soft-tissue sarcomas. Neuropathic pain associated with such tumours can be quite debilitating. We present the case of a 62-year-old woman with chronic neuropathic pain refractory to pharmacologic interventions in association with recurrent pleural leiomyosarcoma. Pulsed radio-frequency of the stellate ganglion was performed after due consideration and planning as a palliative measure to provide pain relief. The patient was discharged the same day with pain score 0/10 and follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…They also showed functional improvement, and used fewer rescue pain killers compared with the PRF group in the 6‐month follow‐up period 56 . Recently, the application of PRF of SG was reported in a 62‐year‐old woman with chronic nerve pain due to pleural malignant tumor encasing the cervical nerve roots 57 . It was found that the VAS score was 0/10 after SG PRF and at the 3‐year follow‐up 57 …”
Section: Sgi Indications and Effectsmentioning
confidence: 98%
See 3 more Smart Citations
“…They also showed functional improvement, and used fewer rescue pain killers compared with the PRF group in the 6‐month follow‐up period 56 . Recently, the application of PRF of SG was reported in a 62‐year‐old woman with chronic nerve pain due to pleural malignant tumor encasing the cervical nerve roots 57 . It was found that the VAS score was 0/10 after SG PRF and at the 3‐year follow‐up 57 …”
Section: Sgi Indications and Effectsmentioning
confidence: 98%
“…TRF 57 Prospective randomized trial Perform nerve release for 60 s at 80°C, then repeat twice after needle tip rotation.…”
Section: Pmpsmentioning
confidence: 99%
See 2 more Smart Citations